House Prices and Macroprudential Policy in an Estimated DSGE Model of New Zealand - Michael Funke; Robert Kirkby; Petar Mihaylovski (Center for Economic Studies and ifo Institute (CESifo), 2017)
We analyse the effects of macroprudential and monetary policies and their interactions using an estimated dynamic stochastic general equilibrium (DSGE) model tailored to New Zealand. We find that the main historical drivers of house prices are shocks specific to the housing sector. While our estimates show that monetary policy has large spillover effects on house prices, it does not appear to have been a major driver of house prices in New Zealand. We consider macroprudential policies, including the loan-to-value restrictions that have been implemented in New Zealand. We find that loan-to-value restrictions reduce house prices with negligible effects on consumer prices, suggesting that they can be used without derailing monetary policy. We estimate that the loan-to-value restrictions imposed in New Zealand in 2013 reduced house prices by 3.8 per cent and that greater forward guidance on their duration would have made them more effective.
Keywords: E32; E44; E52; E58; 330; macroprudential policies; housing; DSGE; Bayesian estimation; New Zealand